A Description Of Satisfaction In Grade 3 Patients Of Food Service At Rsu Private X Bengkulu - Rabiul Armala Sari Nande Putri; Hesti Nur'Aini; Andwini Prasetya; Methatias Ayu Moulina (UNIVED Press, Dehasen University Bengkulu, 2023)
RSU private X Bengkulu is one of general hospital in Bengkulu provides various health services, including outpatient, emergency units, and inpatient care. In the inpatient service unit there is a class 3 treatment room which is an option for patients with a fairly cheap and affordable cost, but the existing facilities are different from other rooms. This study aims to analyze the level of satisfaction and nutritional value of food menus for class 3 patients at RSU private X Bengkulu. The respondents involved were 75 patients who were treated at RSU private X Bengkulu with a descriptive analysis using a Likert scale. The results showed that the level of patient satisfaction with services at RSU private X Bengkulu was 4.08 with the assessment criteria being satisfied from the indicators of satisfaction, responsiveness (responses), confidence (belief), empathy, tangible, reliability, according to diet, food portions, suitability, and cleanliness of equipment. Nutritional Value of Food Grade 3 patients served have a Calorific Value between 1,800.63 Calories/day.